Effect of pregnancy on packed cell volume and total white blood cells count among Sudanese pregnant women attending antenatal care at Ribat University Hospital (Khartoum state) - Ahmed, Wafa Mubarak M.; Khalid, Abdurrahman; Musa, O. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: During pregnancy the women undergo several structural and physiological changes almost in all body systems including the hematological profile. The main reported hematological change is the plasma expansion and haemodilution which affect the red blood cells(RBCs) and white blood cells (WBCs) count in addition to other hematological indices including packed cell volume (PCV). The objective of this study was to assess the effect of pregnancy on packed cell volume and white blood cells among Sudanese pregnant women and derive a formula for the normal values in pregnant women in relation to the packed cell volume. Methods: An analytical case control study was conducted in Khartoum state, Sudan 2017. The study included20 Sudanese pregnant women in the second and third trimesters attending the antenatal care at The National Ribat university hospital and 20 Sudanese non-pregnant women in the same age group as control. A questionnaire was used to collect socio-demographic and clinical data.5ml of venous blood was collected in a container containing EDTA. Complete blood count (CBC) was measured by using automated cell counter Sysmex. Results: There was statistically significant decrease in PCV value during 2nd and 3rd trimesters of pregnancy compared to the non-pregnant control group with p values (0.00 and 0.04 respectively), and statistically significant increase in WBCs count during 2nd and 3rd trimesters of pregnancy compared to the non-pregnant control group with p values (0.04 and 0.00 respectively). Also, a progressive increase in WBCs count with gestational age was demonstrated (second trimester 6.65×103/uL, third trimester 7.43×103/uL). The results showed mean WBCs of 7.79×103/uL, when compared to the estimated values the results showed no significant difference with the mean WBCs in 2ndand 3rdtrimesters (p value 0.06 and 0.39 respectively). Conclusions: During pregnancy there was statistically significant decrease in PCV values, statistically significant increase in WBCs count and by considering the haemodilution factor there was a higher increase in WBCs count.